Determination of Physicochemical Properties and Fatty Acid Composition of Tamarindus indica Seeds Oil - Adeleke, A. E.; Onifade, A. P.; Adegbite, A. A.; Sangoremi, A. A.; Isola, O. E. (Progress in Chemical Science Research Vol. 8, 2023)
This study was carried out to analyze the physicochemical properties and fatty acid composition of oil seeds in order to know their suitability for edibility purpose and industrial applications. The physicochemical properties of seed oils were as follows: acid value (5.10), peroxide value (9.60), free fatty acid (2.05), iodine value (82.50), saponification value (279.20), refractive index (1.467) and specific gravity (0.8423). The findings suggested that the low acid value, free fatty acid, and peroxide value of the Tamarindus indica seed oils would make them suitable for household consumption. The fatty acid compositions revealed that seed oil was more nutritionally significant because it included more unsaturated fatty acids (74.0%) and less saturated fatty acids (26.0%), with linoleic acid methyl ester (44.967%) being the most abundant acid. The high levels of unsaturated fatty acid and low levels of saturated fatty acid indicated low cholesterol oil.The results in this study indicated that the oils Tamarindus indica seed might be useful for domestic consumption as well as industrial applications.